JIWA ENTREPRENEURSHIP UNTUK MEWUJUDKAN KETAHANAN PANGAN - Sumastuti, Efriyani (JEJAK: Jurnal Ekonomi dan Kebijakan, 2010)
The agricultural/ agribusiness sector is the centre of the statesâeconomies. This sector contributes a large share of GDP, employs a large proportion of the labor force, represents a major source of supplies the basic food, and provides subsistence and other income for the large rural populations.Food security, or rights to food, is defined as access to sufficient and affordable food which can relate to a single household or to the global population. Despite political commitments to reduce world hunger, the number of people lacking access to the "minimum dietary energy requirements" (World Food Program, 2009). Sustainable of food security need to ask for entrepreneurship and managerial skill on agribusiness agent. That could be real if all of element (farmer, government, businessman, college, and stakeholders) always to cooperation and coordination.